Pengaruh Perbedaan Waktu Penangkapan Terhadap Hasil Tangkapan Jaring Insang di Sungai Batanghari Yang Melintasi Kecamatan Muara Tembesi Kabupaten Batanghari - Najah, Khairun; Filawati, Filawati; Hariski, M.; Lisna, Lisna; Ramdhani, Farhan; Magwa, Rizky Janatul (Jurnal Perikanan Unram, 2025)
Batanghari Regency, Jambi Province, has fisheries potential supported by Batanghari River, the longest river in Sumatera Island. In Muara Tembesi District, especially Tanjung Pasir Village, some people use gill nets to catch fish in the morning and evening, although the optimal fishing time is not yet known. This study aims to determine the effect of different fishing times on the catch of gill nets in the Batanghari River which crosses Muara Tembesi District, Batanghari Regency. The research was conducted in Tanjung Pasir Village, Muara Tembesi District on December 26, 2024 to April 12, 2025. The method used was experimental fishing, the fishing gear used was two units of ¾ inch gill nets. The observed variables include the type, number, weight, length and height of fish, as well as environmental parameters such as temperature, pH, and depth. Data were analyzed using t-test. The results showed that the morning time produced a catch of 1,161 fish weighing 6,461 grams, an average of 77.40 fish weighing 430.73 grams per repetition. While the afternoon produced 454 fish weighing 2,571 grams, an average of 30.20 fish weighing 171.40 grams per repetition. The results of the t-test analysis showed that fishing time had a significant effect on the number and weight of catches (P<0.05). It can be concluded that the operation of gill nets in the morning produces higher catches, both in terms of number (tails) and total weight of the catch, compared to the afternoon time.